Bone union and mobility outcomes for reconstructed open tibial fractures: a plastic surgical experience from a major trauma center - Sreedharan, Sadhishaan; Bruscino-Raiola, Frank; Lew, Philip; Ling, Yuan; Ferris, Scott (Frontiers in Surgery, 2024)
Introduction: The goal in open tibial fracture management is to achieve a united tibia in an extremity that allows pain free mobilization. The objective of this study was to assess factors that lead to this functional outcome in lower limb reconstruction, from a plastic surgical perspective. Materials and methods: The Plastic and Reconstructive Surgery lower limb database at a tertiary trauma hospital was searched for open tibial injuries from February 2015 to March 2020. The nature and severity of injury, timing and details of all operations including reconstructions were collected prospectively. Mobility including gait aids, pain, and complications were retrospectively collected. Union was assessed in two ways, depending on fracture location. Metaphyseal and diaphyseal tibial fractures were provided mRUST scores (union defined as RUST > 13) and epiphyseal tibial fractures were categorically classified as “united” or “non-union” by two independent radiologists. Results: During the five-year study period there were 148 open leg injuries in the database. Twenty-one patients underwent a primary amputation due to severity of their initial injury. One hundred patients underwent primary limb salvage. Sixty-one patients in the limb salvage group achieved primary tibial union with a mean follow-up time of 19.4 months post injury. Twenty-three additional patients were confirmed to subsequently unite. Patient who achieved union were more likely to mobilise without gait aids. Discussion: In this study definitive external fixation and soft tissue infection were both associated with higher rates of non-union. Longer times to soft tissue reconstruction was not associated with an increase in acute soft tissue complications. More importantly bone union, pain and mobility did not decline. After undertaking a primary limb salvage pathway for 100 patients, the ultimate tibial fracture union rate was 84% and the confirmed ambulation rate was 96%.